2019
DOI: 10.3390/atmos10110644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Typhoon-Generated Cold Wake on the Subsequent Typhoon Tembin and Its Sensitivity to Horizontal Resolutions

Abstract: Weather research models have been used to investigate the sensitivity of simulations of Typhoon Tembin (1214) to changes in three horizontal grid spacings and the effect of the cold wake generated by Typhoon Bolaven (1215). We used modified sea surface temperature (SST) to simulate Tembin as it approached after Bolaven had passed through the Ieodo Ocean Research Station and the Yellow Sea buoy in Korea. In the tropical cyclone (TC) tracking experiments, a higher resolution showed the faster and more eastward m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Negative wind stress curl-induced Ekman pumping and surface flow convergence are the two major processes causing downwelling during and after a TC. This presents a broad view of the possible changes in the thermal structure of the upper ocean in the aftermath of a TC, which could in turn significantly impact oceanic preconditioning and subsequently affect the intensity of upcoming TCs 57 , 58 . Coupled ocean–atmosphere models improve TC forecasts significantly by incorporating the ocean impact into the model, which is particularly notable in slow-moving TC cases 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…Negative wind stress curl-induced Ekman pumping and surface flow convergence are the two major processes causing downwelling during and after a TC. This presents a broad view of the possible changes in the thermal structure of the upper ocean in the aftermath of a TC, which could in turn significantly impact oceanic preconditioning and subsequently affect the intensity of upcoming TCs 57 , 58 . Coupled ocean–atmosphere models improve TC forecasts significantly by incorporating the ocean impact into the model, which is particularly notable in slow-moving TC cases 59 , 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the SST gradient affects the TC track and evolution, and the intensity of TC (Chang & Madala, 1980; Choi et al., 2013; Moon & Ha, 2019). In addition, many previous studies have examined large‐scale factors (e.g., upper tropospheric jet stream, strong vertical wind shear, SST gradient, and western North Pacific (WNP) high) affecting TC activity and track over mid‐latitudes in the WNP (Ho et al., 2009; Ho & Kim, 2011; Kim, Ho, & Sui, 2005; Kim, Sui, & Park, 2005; Moon & Ha, 2019). Particularly, with respect to the KP, several previous studies have investigated the volatility of long‐term trends, the relationship between TCs and the abovementioned factors affecting the TC activity and tracks, and its economic effects (Choi & Kim, 2019; Choi & Moon, 2012; Goh & Chan, 2012; Ho & Kim, 2011; Kim et al., 2019; Lee et al., 2019; Park et al., 2011, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The major factors influencing TC tracks include sea surface temperature (SST), steering flow, beta effect, baroclinic forcing (such as ambient vertical shear and convective heating), and binary interaction (Chan, 2005; Wang et al., 1998). In particular, the SST gradient affects the TC track and evolution, and the intensity of TC (Chang & Madala, 1980; Choi et al., 2013; Moon & Ha, 2019). In addition, many previous studies have examined large‐scale factors (e.g., upper tropospheric jet stream, strong vertical wind shear, SST gradient, and western North Pacific (WNP) high) affecting TC activity and track over mid‐latitudes in the WNP (Ho et al., 2009; Ho & Kim, 2011; Kim, Ho, & Sui, 2005; Kim, Sui, & Park, 2005; Moon & Ha, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have examined devastating typhoons like those mentioned above, and found that the anomalous tracks and extreme rainstorms of TCs can be caused by the interaction of two typhoons, together referred to as a binary tropical cyclone (BTC) (Wu et al 2012;Zhou et al 2014;Fan et al 2014;Xu and Du 2015;Yu et al 2015;Xie et al 2016;Yu and Su-brahmanyam 2017;Moon and Ha 2019). BTC interaction, also known as the "Fujiwara effect", refers to the phenomenon of two cyclonic vortices, which are situated close to each other, simultaneously performing a mutual counterclockwise spin and gradually moving closer to each other (Fujiwhara 1921(Fujiwhara , 1923(Fujiwhara , 1931.…”
Section: Introductionmentioning
confidence: 99%